The Influence of Quantum Teaching Learning Model on Students Learning Outcomes in Grade VI with Subtheme 2 Discovery and Benefits in SDN 097805 Rambung Merah - Enggani Manullang; Minar Trisnawati Tobing; Selamat Triadil Saragih (International Journal of Integrated Science and Technology, 2023)
This research aims to determine the influence of the model QUANTUM TEACHING  on the learning outcomes of Class VI elementary school students, Subtheme 2 Discovery and its benefits. At SD Negeri 097805 Rambung Merah , the method in this research is a quantitative experimental type method whose research design is pre-experimental, one group pretest-posttest type. This was carried out on October 30 to October 31 2023. The population in this study were all class VI students at SD Negeri 097805 Rambung Merah. The sample used was purposing sampling with two research variables: the dependent variable (x) in the form of learning outcomes, and the independent variable ( y) in the form of a model Quantum Teaching. Data collection techniques are test techniques with validity tests, reliability tests, difficulty level tests, and differentiating power tests. The results of hypothesis testing using the normality test, homogeneity test, and T-test with the help of the SPSS version 2 6 program, with the result t = 15.711 with a significance level (2-tailed) 0.000, significant probability <0.05, t count >t table = 15.711>2.064 then HO is rejected and Ha is accepted. This explanation shows that there is an influence of the Quantum Teaching Learning Model on the learning outcomes of class students in theme 3 class VI of SD Negeri 097805 Rambung Merah.